The use of politeness strategies by pharmacy students while obtaining information from patients during OSCES consultations. (30th November 2022) - Alsubaie, S; Grant, D; Donyai, P
Abstract: Introduction: Objective Structured Clinical Examinations (OSCEs) assess students' application of clinical and communication skills, and can include discussing patient behaviours (e.g., diet, or medication adherence). Politeness Theory (PT) defines potentially sensitive elements of such interactions as Face Threatening Acts (FTAs) and proposes a framework of mitigating Politeness Strategies (PS). Accordingly, asking a behavioural question, e.g. 'have you been taking your medicines?', interferes both with the person's face need to be autonomous and face need to be 'liked', by imposing a response and risk of judgement, respectively. Contrastingly, fact-finding questions (e.g. 'what is your name?') are arguably less face threatening because they don't hinge on patient behaviours. Asking a question directly without attempting to minimize its impact on face needs is usually considered devoid of PS (labelled within PT as a 'Bald on record' approach), whereas for example hedging (e.g. using 'perhaps'), showing deference (e.g. 'please') and being indirect (e.g. 'would you happen to know') involve PS. Not meeting patient face needs can create tension, cause distress and, in turn, decrease the effectiveness of an interaction. We hypothesised students would use PS more frequently when asking questions relating to patient behaviours (i.e. involving obvious FTAs) compared to standard non-behavioural questions, in order to maintain patient face. Aim: To identify behavioural and non-behavioural questions asked by pharmacy students and any PS used within recorded OSCEs, and test differences between question types and use of PS. Methods: This study employed PT to identify any conversational PS used by students. Following institutional ethical approval, a total of 19 OSCE video recordings of 10 students performing Healthy Living Assessments (HLA) and Responding to Symptoms (RTS) scenarios were transcribed using ELAN software ((Version 6.4). Student speech activities were coded as behavioural or non-behavioural questions. PS used by students were classified as absent (i.e. 'Bald on record') or using at least one PS. We looked for associations between categories of questions (behavioural or non-behavioural) and use of PS (absent or present) using the Chi-square test. Results: In most cases, pharmacy students used the 'Bald on record' approach to obtain information; 63 % for behavioural questions, e.g. "what is your alcohol intake?" or "do you smoke cigarettes?", and 60% for non-behavioural questions, e.g. "do you have any food or drug allergies?". PS were also used, but with lower frequency; 37% for behavioural questions, e.g. by asking the patient's permission politely "is it okay to ask you some questions about your lifestyle...?", and 40% for non-behavioural questions, e.g. "may I ask you how old are you?". The Chi-square test (χ 2 =1.98, df=1, p =0.73) showed no significant relationship between the face threatening nature of a question and the use of PS. Discussion/Conclusion: Pharmacy students asked behavioural questions similar to how they asked non-behavioural questions, and may be unaware that behavioural (vs. non-behavioural) questions are potentially more face threatening to patients. Enhancing pharmacy students' awareness of patient face needs and PS is a novel approach, which could be explored further when teaching about consultations with its impact tested in future research. References: 1. Brown P, Levinson SC. Politeness: some universals in language usage . vol 4. Cambridge University Press; 1987. 2. Have P. Doing conversation analysis . 2nd ed. Introducing qualitative methods. Sage; 2007.